Health-related quality of life implications of plantar ulcers resulting from neuropathic damage caused by leprosy: An analysis from the trial of autologous blood products (TABLE trial) in Nepal. - Naomi Kate Gibbs; Jessica Ochalek; Indra Bahadur Napit; Dilip Shrestha; Pedro Saramago Goncalves; Richard J Lilford; Mark Sculpher (PLoS ONE)
Introduction Leprosy is a curable disease, treated by multidrug therapy. However, patients are often left with neuropathic damage leading to lifelong vulnerability to ulcers. Quantifying the value of interventions to improve ulcer healing is challenging as data on the health impact of plantar ulcers are scarce, especially in low- and middle-income countries. We aim to quantify the impact of plantar ulcers on patients' health-related quality of life (HRQoL) using methods which can inform decisions about the effectiveness and cost-effectiveness of alternative forms of management. Methods Generic HRQoL data were collected using the EuroQol (EQ)-5D-3L questionnaire in a randomised control trial in Nepal, treating plantar ulcers with leukocyte and platelet-rich fibrin or usual care. The trial followed 130 patients resulting in 600 observations. EQ-5D data were converted into a single 'utility' score by weighting the instrument's different dimensions using the preferences of the Sri Lankan population. Utility data were analysed using general estimating equation regressions. The impact of an ulcer on HRQoL was estimated whilst controlling for clinical and demographic covariables. Results Estimated mean utility (standard error) for the sample across all time points was 0.52 (0.02) for patients with an ulcer and 0.64 (0.01) with a healed ulcer. Controlling for clinical and demographic covariates, we estimate that the presence of an ulcer leads to a 0.12 (0.02) decrement in HRQoL compared with a healed ulcer. Discussion Based on the levels of health they report and the values of the general public, patients with a history of leprosy are at risk of significant HRQoL burden from neuropathic plantar ulcers. Quantifying this health impact provides important evidence to assess the effectiveness and cost-effectiveness of leprosy ulcer interventions and ensures that interventions for leprosy ulcers can be appropriately considered for funding under Universal Health Coverage against other potential uses of the same money.